THE ROLE OF KNOWLEDGE MANAGEMENT IN ENHANCING PRODUCT INNOVATION: AN EMPIRICAL STUDY OF THE CREATIVE INDUSTRY IN INDONESIA - Mashudi; Fauziah, Luluk (Branding: Jurnal Manajemen dan Bisnis, 2024)
The creative industry in Indonesia is growing rapidly, and digital transformation is driving innovation in various sectors. Knowledge management is an important factor in creating innovative products that can compete in the global market. However, there are still challenges in optimizing knowledge management strategies to increase the competitiveness and sustainability of the creative industry. This study aims to analyze the role of knowledge management in driving product innovation in the Indonesian creative industry. The research method used is a qualitative approach, which involves collecting data from various previous studies, industry reports, and relevant academic research. The data obtained are then analyzed systematically to identify the relationship between knowledge management and product innovation. The results of the study show that an effective knowledge management strategy contributes to improving the quality, efficiency, and sustainability of product innovation in the creative industry. A work environment that supports the exchange of ideas, the use of digital technology, and cross-sector collaboration are the main factors in strengthening the knowledge-based innovation ecosystem. Therefore, optimizing knowledge management must be a priority in the creative industry development strategy to remain competitive in the global market.